Inpatient Postpartum Long-Acting Reversible Contraception: Care That Promotes Reproductive Justice. Issue 4 (October 2017) - Moniz, Michelle H.; Spector-Bagdady, Kayte; Heisler, Michele; Harris, Lisa Hope
Abstract : Inpatient insertion of long-acting reversible contraceptives (LARC) (intrauterine devices and implants) is increasingly offered to women immediately after childbirth. Enthusiasm for this approach stems from robust safety, effectiveness, and cost-effectiveness data and responsiveness to women's needs and preferences. Although clinical evidence for immediate postpartum LARC is well-established, the ethical implications of enhancing access to this care have not been fully considered. Contraceptive policies and practices often embody a tension between fostering liberal availability and potentially coercive promotion of some methods. Historical contraceptive policies and contemporary disparities in LARC use point to the need to consider whether health policies and health care practices support all women's reproductive wishes. Immediate postpartum LARC services need to be designed and implemented with the goal of ensuring autonomy and equity in postpartum contraceptive care. To this end, these services should include strategic plans to promote universal availability, prevent coercion, and enable device removal. Abstract : To ensure autonomy and equity, immediate postpartum contraceptive services should include strategic plans to promote universal availability, prevent coercion, and enable device removal.